2018
DOI: 10.1289/ehp2358
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Phthalates, Maternal Thyroid Function, and Risk of Attention-Deficit Hyperactivity Disorder in the Norwegian Mother and Child Cohort

Abstract: Background:There is growing concern that phthalate exposures may have an impact on child neurodevelopment. Prenatal exposure to phthalates has been linked with externalizing behaviors and executive functioning defects suggestive of an attention-deficit hyperactivity disorder (ADHD) phenotype.Objectives:We undertook an investigation into whether prenatal exposure to phthalates was associated with clinically confirmed ADHD in a population-based nested case–control study of the Norwegian Mother and Child Cohort (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 86 publications
5
71
2
Order By: Relevance
“…In the first study, we selected 506 ADHD cases and 657 controls, frequency matched on birth year and sex to the case group. The second study included 199 ADHD cases and 529 controls matched on birth year but not sex (see Engel et al). Because of this slight difference in selection methods, all analyses were adjusted for or stratified by child sex.…”
Section: Methodsmentioning
confidence: 99%
“…In the first study, we selected 506 ADHD cases and 657 controls, frequency matched on birth year and sex to the case group. The second study included 199 ADHD cases and 529 controls matched on birth year but not sex (see Engel et al). Because of this slight difference in selection methods, all analyses were adjusted for or stratified by child sex.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies suggest that phthalate exposure during pregnancy is associated with increased risk of pregnancy loss, preeclampsia, preterm birth, and gestational hypertension [3][4][5][6][7][8][9]. In addition, gestational phthalate exposure has been associated with altered neurodevelopment [10][11][12][13], endocrine, reproductive [14][15][16][17][18], and cardiometabolic outcomes during infancy and childhood [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is hypothesized that prenatal exposure to phthalates might contribute to risk of childhood neurodevelopmental disorders. Among children 8–11 years of age, urinary concentrations of di(2-ethylhexyl) phthalate (DEHP) metabolites were significantly associated with attention deficit hyperactivity disorder (ADHD) [ 33 , 34 ]. Other studies also found that having PVC flooring (a source of certain phthalates) in a parent’s bedroom during pregnancy and child’s first year was associated with an increased risk of ASD [ 35 ] and that higher indoor dust concentrations of diethyl phthalate (DEP) and dibutyl phthalate (DBP) were associated with greater hyperactivity-impulsivity and inattention among ASD children [ 36 ].…”
Section: Introductionmentioning
confidence: 99%